Effect of Chitooligosaccharide Characteristics from Several Types of Shells on Prebiotic Activity : A Brief Review: Pengaruh Karakteristik Chitooligosakarida dari Beberapa Macam Cangkang Terhadap Aktivitas Prebiotik : Review Singkat - Patrisiya, Berta; Oktavia, Nanda; Zhorif , Muhammad Naufal; Priyanto, Anugerah Dany (jurnal makanan tropis dan teknologi agroindustri, 2023)
Seafood is one of the foods favored by the community and has waste that is not used properly, such as shells. The component contained in the highest shell is chitin, this chitin content can be processed into chitosan. Chitosan is obtained from a process, namely enzymatic and chemical hydrolysis and this process can also be used to obtain chitooligosaccharides. Chitooligosaccharides are complex compounds of the glycoprotein group which have -1,4 glucosamine bonds. Chitooligosaccharides can act as prebiotics. Recently, there has been a lot of research on the characteristics and prebiotic activity of chitooligosaccharides. However, there is a lack of information regarding the relationship between the characteristics and prebiotic activity of chitooligosaccharides mainly from different sources of chitooligosaccharides. Therefore, the aim of this review is to summarize and collect viewpoints regarding the relationship of characteristics with prebiotic activity. The characteristics of chitosan of each type of shell have differences, the main parameter is the degree of deacetylation. The high degree of deacetylation and yield can affect the yield on the characteristics of the chitooligosaccharides produced. Thus, the higher the degree of deacetylation of chitosan, the higher the degree of deacetylation of chitooligosaccharides, so that it can show high prebiotic activity because probiotic bacteria can grow well. Accordingly, this summary can contribute to explaining a comprehensive review of the characteristics of chitooligosaccharides on the prebiotic activity of underutilized and safe materials for consumption.